LANDASAN METODOLOGIS TEOLOGI PENDIDIKAN ISLAM - Undang Burhanudin (The Faculty of Tarbiyah and Teacher Training associated with PSPII, 2012)
This paper aims to describe that there is a number of conventions/rules that must be considered by the researcher of Islamic education in interpreting the verses of the Qur'an related to education. The conventions/rules can be in the form of methodological and theological. Methodologically, an attempt to interpret the verses of education contained in the Qur'an comes from the Qur'an interpretation methods. In general, the method of interpretation of the Qur'an is not different from the method of interpreting the text/script in general. The most distinguishing thing is the text itself in the form of the holy book. Therefore, there needs to be a certain theological understanding to treat the holy Qurán as an object of study/interpretation/research. The Qur'an is the word of Allah SWT that contains instructions for all humans. As the word of Allah, only God knows all intents contained in each verse of the Qur'an. But as a guide, the word must be understood in order to be carried out. On that basis, efforts to understand the Qur'an should be done, includingto understand the verses of the Qur'an related to education. Variety of these efforts including the basic principles, methods of analysis and research methods are summarized in the concept of theology methodological foundation of Islamic education.